Analisis Kinerja Keuangan Pada Koperasi Kelompok Wanita Kerto Mulyo Periode Laporan 2015 - 2019 - Angguliyah; Wibowo, Doni Teguh; Sinollah (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2023)
In this research activity, measurement of financial performance is carried out using ratio analysis including liquidity, solvency and profitability. Data was collected at the Kerto Mulyo Women's Group Cooperative from 2015 - 2019. The research approach used quantitative methods, data sources and research objects were obtained based on the annual report of the Kerto Mulyo Women's Group Cooperative. The results of the analysis that has been carried out are obtained by measuring the financial performance of Cooperatives for Liquidity Ratios through current ratios and cash ratios. Measurement through the current ratio gives financial performance results in a very healthy condition, while measurement through the cash ratio is in an unhealthy condition. Furthermore, for the results of the analysis that has been carried out, it is obtained a measure of the Cooperative's financial performance for the Solvability Ratio through Debt to Equity Ratio (DER) and Debt to Asset (DAR). Performance measurement through Debt to Equity Ratio (DER) results are obtained in a healthy condition, while measurements through Debt to Asset (DAR) are in a healthy condition. Furthermore, the financial performance of Cooperatives for Profitability Ratios is measured through Return on Equity (ROE) and Return on Assets (ROA). Measurements through Return on Equity (ROE) obtained healthy financial performance conditions, while measurements through Return on Assets (ROA) were in fairly healthy condition. Measurement through Net Profit Margin (NPM) is in very good condition.